No one sleeps in Alexandria - ʻAbd al-Majīd, Ibrāhīm (American University in Cairo Press, 2006)
This sweeping novel depicts the intertwined lives of an assortment of Egyptians-Muslims and Copts, northerners and southerners, men and women-as they begin to settle in Egypt's great second city, and explores how the Second World War, starting in supposedly faraway Europe, comes crashing down on them, affecting their lives in fateful ways. Central to the novel is the story of a striking friendship between Sheikh Magd al-Din, a devout Muslim with peasant roots in northern Egypt, and Dimyan, a Copt with roots in southern Egypt, in their journey of survival and self-discovery.